Two-Dimensional PtS2/MoTe2 van der Waals Heterostructure: An Efficient Potential Photocatalyst for Water Splitting - Shao, Changqing; Ren, Kai; Huang, Zhaoming; Yang, Jingjiang; Cui, Zhen (Frontiers in Chemistry, 2022)
Recently, the energy shortage has become increasingly prominent, and hydrogen (H2) energy has attracted extensive attention as a clean resource. Two-dimensional (2D) materials show excellent physical and chemical properties, which demonstrates considerable advantages in the application of photocatalysis compared with traditional materials. In this investigation, based on first-principles methods, 2D PtS2 and MoTe2 are selected to combine a heterostructure using van der Waals (vdW) forces, which suggests a type-II band structure to prevent the recombination of the photogenerated charges. Then, the calculated band edge positions reveal the decent ability to develop the redox reaction for water splitting at pH 0. Besides, the potential drop between the PtS2/MoTe2 vdW heterostructure interface also can separate the photogenerated electrons and holes induced by the charge density difference of the PtS2 and MoTe2 layers. Moreover, the fantastic optical performances of the PtS2/MoTe2 vdW heterostructure further explain the promising advanced usage for photocatalytic decomposition of water.